Giloye - Root of Immortality for Past, Present & Future in Affordable Price (AYUSHDHARA, 2025)
Aim: An explicit study of Giloye (Tinospora cordifolia Wild. & Miers.) to find out its safety and solution to the loopholes that are preventing its multidimensional therapeutic efficacy from spreading globally. Material and method: Information regarding the Giloye (Amrita) was collected from various ancient works of literature, Nighantu (lexicons of medicinal plants), recent journals, and information was also gathered from the internet. For various references like Vedic and mythological references, text related to Dravyaguna and published articles were referred to. Result: From the above study, it was concluded that Giloye "The magical herb" is an Amrita (elixir) for humankind because of its easy propagation, affordable price, diverse uses, and effective pharmacological action. No significant information is available on Giloye regarding toxicity on therapeutic dosage. But we noticed from the above study that we must focus on some important points like Dissemination of identity of herbs to the public, Digitalization of pharmacovigilance program. Conclusion: Herbs like Guduchi are popular and is being used for various disorders for many years. Various researches was also conducted on Guduchi which proves its safety and efficacy. Thus, it is reiterated that “Guduchi” ayurvedic herb is safe and cost-effective however it should be used after proper consultation from Ayurvedic medical practitioners. If rules and regulations or proper platforms like mentioned below are not made for use of Giloye or any other herb or Ayurvedic formulation, then the day is not due when a tragedy like thalidomide will be in front of us in Ayurveda itself.